Hearing Development in Early Childhood: Compendium of Scientific Evidence Relevant to the Teaching Staff - Angel-Alvarado, Rolando (2017)
This article aims to know about hearing development experienced by otologically healthy children during their early childhood, in order to give an objective documentation about the matter to preschool education teachers, so that they can improve and enhance their didactic work in the classroom. The research uses classic bibliography in health sciences and psychology, international standards on hearing thresholds, and validated researches addressing the development of tonal discrimination, localization of sounds in space, and the impact of hearing on integral child development. It is concluded that the hearing development in early childhood is not limited to physiological aspect, but it also involves other factors such as sensory, sensorimotor, perceptual and cognitive ones.